Ciclo hidrográfico planetário: abordagens e conceitos - de Miranda, Ricardo Augusto Calheiro; de Oliveira, Marcus Vinícius Siqueira; da Silva, Danielle Ferreira (Geo UERJ, 2010)
doi: 10.12957/geouerj.2010.1461